2018
DOI: 10.2147/cmar.s166437
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of cancer diagnosis in China: the incidence, patients’ situation, and different preferences between patients and their family members and related influence factors

Abstract: PurposeThe purpose of this study was to investigate the disclosure incidence of cancer diagnosis to patients before chemotherapy, to survey the attitudes of the patients and their families and related influencing factors toward disclosure of cancer diagnosis, and to compare the anxiety and depression levels between the disclosure and non-disclosure patients.Participants and methodsA prospective cohort study was conducted at a tertiary hospital in China. A consecutive series of patients who had been diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…Physicians in China should realize the different attitudes toward CDD between patients and family members. 15 Similar results have been presented in other studies. 16,17 Moreover, Gan's quantitative study…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Physicians in China should realize the different attitudes toward CDD between patients and family members. 15 Similar results have been presented in other studies. 16,17 Moreover, Gan's quantitative study…”
Section: Introductionsupporting
confidence: 89%
“…Our former study also found that cancer patients' views of diagnosis disclosure were different from those of their family members. Physicians in China should realize the different attitudes toward CDD between patients and family members . Similar results have been presented in other studies .…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations